Rede e serviços de atendimento em saúde : percepções de profissionais e mulheres usuárias de crack - Maciel, Luisa Zamagna (2017)
The high prevalence of crack use in Brasil is considered a public health problem. The usage of crack among women embraces social, cultural, psychological, medical and legal areas, bringing several consequences for their lives. The development of guidelines, actions and suitable strategies to assist this population is key factor for elaboration of efficient treatment. This study has the objective to evaluate crack cocaine-dependent women perception about health care professionals regarding the assistance provided in public health system. This thesis is composed by two empirical articles. The first article aimed to evaluate the perception of crack cocaine-dependent women users through content analysis of 12 interviews. Among the public health care services provided, it was possible to categorize the speech into positive and negative perceptions, as well as recommendations and possible improvements. Among the positive perception, women mentioned the multidisciplinary assistance as more caring. Among the negative side, the waiting lists for assistance was brought as something that discourage the population in looking for treatment. Related to improvements suggested, women mentioned that professionals needed to have better working conditions in order not to interfere negatively on their approaches towards them. In addition, they suggested continuous training for these professionals. The second article evaluated the perception of the health care professionals about crack cocaine-dependent women and about the public health services for this population. Three focus groups were conducted, totalizing 33 healthcare professionals from São Paulo and Porto Alegre. Through thematic analyses, it was identified two main axis. In the first axis, named as “Crack female users”, it was described characteristics that professionals identified as prevalent in crack cocaine women, such as low educational level, unemployment, lack of social and familiar support, violence background history and social and gender stigmas. In the second axis, named as “Public healthcare services”, it was described how professionals see the health system flow, which contains certain difficulties, mainly regarding the lack of women focused service. Regarding interventions, it was possible to notice the commitment from the professionals in driving the assistances which contributed to women higher adherence in the services. In the limitations, it was observed the difficulty of professional of basic attention to attending the women, highlighting the necessity to improve the attending of women who were crack users. These results are relevant to understand the possible repercussions of the health services and care provided to this population. In the medium term, the results will support the development of a brief manual and training for practitioners with a view to enhancing effective interventions for the specific demands of women. Conclusions: It is possible to observe that both studies are complementary. The view crack cocaine-dependent women and professionals are similar regarding the difficulties encountered in public health services and about the need of professionals to have adequate working conditions and continuous training.